KINERJA PLASTIC OPTICAL FIBER (POF) JENIS STEP INDEX MULTIMODE DALAM SUHU RENDAH PADA SISTEM KOMUNIKASI SERAT OPTIK - Hanif Yahya Muhatdin; Sholeh Hadi Pramono; Gaguk Asmungi (Jurnal Mahasiswa TEUB, 2015)
One of the problems that can affect the performance of optical fiber transmission network is a change in environmental temperature. Significant changes in temperature, too high or too low causes a change in the trajectory of propagation of light in optical fiber due to changes in the value of the refractive index of core and cladding. Sellmeier equation states that rising temperatures will lead to the increase in refractive index. This will give you the consequences of the change in Numerical Aperture (NA), the acceptance angle, and the refraction angle of light, and will affect the system performance. In this research by experimental study on the effect of low temperatures on the Bit Error Rate (BER) and eye pattern on POF types of multimode step-index. The losses value are affected by variations in low temperature value given. The experimental results showed that there was a change exponentially of BER values to changes in temperature. This error is shown at a temperature of 25oC to -10oC with BER value respectively is 3.1380 x 10-6 and 3.1630 x 10-6. the noise value increase at a temperature of 25oC to -10oC with the value of SNR 22,35 dB and 21,16dB, the value of noise margin 88.08% and 85.80%, the value of timing jitter 3.19% and 4.68%, and the value of the bit rate showed little change that is equal to 31,867 Kbps to 31,616 Kbps between the temperature of 25oC to -10oC.Index Terms—Low Temperature, POF, SNR, BER, Noise Margin, Timing Jitter